PEMERIKSAAN KESEHATAN PADA LANSIA DI DUSUN RINGINSARI BOKOHARJO PRAMBANAN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - TUTIK ASTUTI (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2021)
Background: Cervical cancer is the second cancer in the world that affects most women after breast cancer, especially in developing countries such as Indonesia. Factors that make the early detection done by women due to lack of knowledge about cervical cancer, for example to maintain the cleanliness of the female area (vagina) is very important, especially for women and how to detect early so that women are not affected by cervical cancer. Objective: To determine the differences in Pre and Post knowledge of Health Counseling about Cervical Cancer in Women in Ringinsari Bokoharjo Prambanan Sleman Special Region of Yogyakarta Method: The method used is a quasi experiment with the